Recent Progress Toward Hydrogen Medicine: Potential of Molecular Hydrogen for Preventive and Therapeutic Applications - Ohta, Shigeo (Current Pharmaceutical Design, 2011)
Persistent oxidative stress is one of the major causes of most lifestyle-related diseases, cancer and the aging process. Acute oxidative stress directly causes serious damage to tissues. Despite the clinical importance of oxidative damage, antioxidants have been of limited therapeutic success. We have proposed that molecular hydrogen (H2) has potential as a “novel” antioxidant in preventive and therapeutic applications [Ohsawa et al., Nat Med. 2007: 13; 688-94]. H2 has a number of advantages as a potential antioxidant: H2 rapidly diffuses into tissues and cells, and it is mild enough neither to disturb metabolic redox reactions nor to affect reactive oxygen species (ROS) that function in cell signaling, thereby, there should be little adverse effects of consuming H2. There are several methods to ingest or consume H2, including inhaling hydrogen gas, drinking H2-dissolved water (hydrogen water), taking a hydrogen bath, injecting H2- dissolved saline (hydrogen saline), dropping hydrogen saline onto the eye, and increasing the production of intestinal H2 by bacteria. Since the publication of the first H2 paper in Nature Medicine in 2007, the biological effects of H2 have been confirmed by the publication of more than 38 diseases, physiological states and clinical tests in leading biological/medical journals, and several groups have started clinical examinations. Moreover, H2 shows not only effects against oxidative stress, but also various anti-inflammatory and antiallergic effects. H2 regulates various gene expressions and protein-phosphorylations, though the molecular mechanisms underlying the marked effects of very small amounts of H2 remain elusive.
Keywords: ischemia-reperfusion